NEW VERSION OF THE MAGNETIC CURVES ACCORDING TO THE BISHOP FRAME IN E-3 - Sariaydin, Muhammed T.; Körpınar, Talat (HONAM MATHEMATICAL SOC, 2019)
In this paper, it is investigated Lorentz force equations for N-1 and N-2-magnetic curves in 3-Dimensional Euclidean space. We give the Lorentz force in the Bishop frame in E-3. Then, we obtain a new characterization for a magnetic field V. Also, we also give examples for each curve.
Keywords: Magnetic curves; Backlund transformations; Killing magnetic field